2006
DOI: 10.1016/j.jcrs.2005.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Keratitis after intracorneal ring segment insertion for keratoconus

Abstract: We report a case of sterile keratitis after Ferrara intracorneal ring (Ferrara Ophthalmics) implantation into the right cornea of a keratoconus patient who also suffered from atopic blepharoconjunctivitis. The keratitis resolved within a few days after removal of the Ferrara rings. Ocular atopy with sterile keratitis should be considered in the differential diagnosis of keratitis after the insertion of intracorneal ring segments, which can be easily treated by ring removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…They linked its presence to rosacea, while two of our cases had spring catarrh. McAlister et al 31 reported another case of sterile keratitis and thought that atopic keratoconjunctivitis can be implicated. In both cases reported, ring removal relieved the case, while in our five cases, medical treatment was sufficient and did not affect the final visual outcome.…”
Section: Discussionmentioning
confidence: 99%
“…They linked its presence to rosacea, while two of our cases had spring catarrh. McAlister et al 31 reported another case of sterile keratitis and thought that atopic keratoconjunctivitis can be implicated. In both cases reported, ring removal relieved the case, while in our five cases, medical treatment was sufficient and did not affect the final visual outcome.…”
Section: Discussionmentioning
confidence: 99%
“…66 The keratitis resolved within a few days after removal of the segment. Ocular atrophy with sterile keratitis should be considered in the differential diagnosis of keratitis after intracorneal ring implantation.…”
Section: Complicationsmentioning
confidence: 98%
“…However, other studies described intrastromal deposits in the lamellar channel around the ring [14,31] and a decrease of the keratocyte density above and below the ring [15] as common clinical and histological findings, respectively. Also, anterior stromal aseptic necrosis, infiltrative keratitis or stromal thinning was reported [32][33][34]. Likewise, the pressure generated inside the stroma after …”
Section: Discussionmentioning
confidence: 99%